Execution - Smith, Alexander Gordon, 1979- (New York : Farrar, Straus and Giroux, 2012)
Alex Sawyer has escaped his underground nightmare to discover that the whole world has become a horrible prison run by his nemesis, Alfred Furnace, and only Alex can stop him, even if that makes him the executioner.
Originally published in Great Britain in 2011 by Faber and Faber.
910
Keywords: Prisons -- Juvenile fiction; Fugitives from justice -- Juvenile fiction; Science fiction; Horror tales